Pre- and Postoperative State of Coagulation and Fibrinolysis in Plasma of Patients with Benign and Malignant Colorectal Disease - A Preliminary Study - Iversen, L H; Okholm, M; Thorlacius-Ussing, O (Thrombosis and Haemostasis, 1996)
This study was carried out in order to compare the coagulation balance in patients with colorectal cancer before and after surgical removal of tumor with an age matched non-malignancy control group. Furthermore, it was studied whether preoperative coagulation state in cancer patients was correlated to the postoperative development of deep venous thrombosis (DVT) diagnosed by venography. Plasma was collected preoperatively in 93 cancer patients and 30 controls, and postoperatively on day one, two, seven, and ninety in 88 cancer patients and 18 controls. Prothrombin fragment 1 + 2 (F1 + 2), thrombin-antithrombin complex (TAT), and total fibrin(ogen) degradation products (TDP) were quantitated in plasma by enzyme linked immunosorbent assays (ELISA). As compared to controls, patients admitted for cancer treatment displayed significantly higher levels of F1 + 2 and TAT. Patients suffering from advanced colorectal cancer had significantly higher levels of TAT and TDP as compared to patients with localized colorectal cancer. Twenty-three percent of cancer patients developed DVT postoperatively. Preoperatively these patients displayed significantly higher TDP levels, and postoperatively higher levels of F1 + 2, TAT, and TDP compared to cancer patients without DVT. The marked activation of blood coagulation and fibrinolysis observed in all patients following major abdominal surgery was even more pronounced in patients not cured for cancer.